Thioester-containing protein TEP15 promotes malaria parasite development in mosquitoes through negative regulation of melanization - Qin, Xin; Li, Jianyong; Zhu, Feng; Zhang, Jian (Parasites & vectors, 2025)
Thioester-containing proteins (TEPs) serve as crucial effectors and regulatory components within the innate immune system of mosquitoes. Despite their significance, the mechanisms by which TEPs exert negative regulation on the immune response in mosquitoes remain inadequately understood. This study aims to elucidate the role of TEPs in the negative regulation of melanization, thereby advancing our comprehension of their regulatory function in the immune response. We infected female Anopheles stephensi mosquitoes with Plasmodium yoelii by allowing them to feed on pre-infected female Kunming mice. Western blot, quantitative polymerase chain reaction, differential gene expression analyses, and gene silencing were then conducted. Student's t-test was used to analyze continuous variables, with statistical significance defined as p < 0.05. A. stephensi TEP15 (AsTEP15) negatively regulated mosquitos' innate immunity and promoted Plasmodium development. AsTEP15 knockdown induced mosquito resistance to malaria parasite melanization during the oocyst stage and significantly reduced sporozoite numbers. Further analysis showed that AsTEP15 mainly negatively affects the TEP1 and immune deficiency (IMD) pathway, thereby inhibiting melanization. We describe a mosquito TEP that negatively regulates immunity, further enriching the functional diversity of TEP family members. In addition, our results suggest that oocysts may exploit TEPs to escape or inhibit mosquito immunity, highlighting potential targets for blocking malaria transmission.